2020
DOI: 10.1111/ajco.13373
|View full text |Cite
|
Sign up to set email alerts
|

End of life experiences of patients with advanced cancer in Myanmar: Results from the APPROACH study

Abstract: Background: Access to palliative care services is essential for attaining universal health coverage for patients with a terminal cancer. Despite this, many patients with advanced cancer in lowincome countries, such as Myanmar, suffer at the end of life (EOL) due to little or no access to palliative care. However, actual evidence on EOL experiences of cancer patients in Myanmar is lacking. This paper aims to describe various dimensions of EOL experiences among patients with an advanced cancer from the largest p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Earlier research from Myanmar revealed that older adults in rural areas have unsafe socio-demographic conditions and low healthcare-seeking behavior [40]. Another study supported that Myanmar cancer patients with low socio-economic status (SES) had a significantly worse quality of life, perceived poor health care coordination, and were more likely to report severe pain than those with high SES [34]. Therefore, it is reasonable to consider that Myanmar patients living in rural areas may encounter a low quality of care and difficulty accessing health care appropriately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research from Myanmar revealed that older adults in rural areas have unsafe socio-demographic conditions and low healthcare-seeking behavior [40]. Another study supported that Myanmar cancer patients with low socio-economic status (SES) had a significantly worse quality of life, perceived poor health care coordination, and were more likely to report severe pain than those with high SES [34]. Therefore, it is reasonable to consider that Myanmar patients living in rural areas may encounter a low quality of care and difficulty accessing health care appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Myanmar, a low-and middle-income country in Southeast Asia, faces insufficient health care services [33], including palliative care delivery [8]. There are only two palliative care units in Myanmar, Yangon General Hospital and Mandalay General Hospital [34]. To increase the utilization rate, we need to understand what factors are associated with patients' willingness to utilize palliative care services.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted in other patient groups or in diverse settings show that pain prevalence is higher among patients who are younger, 6 have lower socio-economic status, 8,9 and after hospitalisation, 10 and that patients with primary tumours in the breast or genitourinary system report higher pain severity/interference. 1,3 Although the World Health Organisation recommends that moderate to severe pain be treated by opioids, 11 many patients and physicians are reluctant to use these due to fear of adverse effects.…”
Section: Introductionmentioning
confidence: 90%
“…We adapted a scale from Ayanian et al 3 We added an additional item: “How often did you feel you were as much involved in decisions about your care as you wanted?” We have used the adapted scale previously 24,25 . The 12 items of the scale were grouped into 2 domains: physician communication (5 items) and care coordination (7 items).…”
Section: Methodsmentioning
confidence: 99%
“…We have used the adapted scale previously. 24,25 The 12 items of the scale were grouped into 2 domains: physician communication (5 items) and care coordination (7 items). Both domains were scored to a 100-point scale, with 0 representing worst care and 100 representing optimal care.…”
Section: Experience With Health Care Practitionersmentioning
confidence: 99%